2021
DOI: 10.1089/acm.2020.0245
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Complementary and Integrative Approaches in Promoting Engagement and Overall Wellness Toward Suicide Prevention in Veterans

Abstract: Objective: Suicide is a major public health problem, specifically among U.S. veterans, who do not consistently engage in mental health services, often citing stigma as a barrier. Complementary and Integrative Health (CIH) interventions are promising alternatives in promoting patient engagement and further, they may play a critical role in transitioning people into mental health care. Toward this goal, the Resilience and Wellness Center (RWC) was developed to break through the stigma barrier by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…In the second step, through a full-text review, nine articles that did not meet the inclusion criteria were excluded. The reasons for the papers excluded in the second step are as follows: a case study of self-injury after acupuncture [ 26 ], a letter to the editor without clinical data [ 27 ], four observational studies [ 28 , 29 , 30 , 31 ], and three not reporting suicidal behaviors as their outcomes [ 32 , 33 , 34 ]. Finally, eight studies in nine articles [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] were included in this review by the two-step selection process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second step, through a full-text review, nine articles that did not meet the inclusion criteria were excluded. The reasons for the papers excluded in the second step are as follows: a case study of self-injury after acupuncture [ 26 ], a letter to the editor without clinical data [ 27 ], four observational studies [ 28 , 29 , 30 , 31 ], and three not reporting suicidal behaviors as their outcomes [ 32 , 33 , 34 ]. Finally, eight studies in nine articles [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] were included in this review by the two-step selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, more than half of the studies [ 35 , 36 , 37 , 38 , 43 ] included in this systematic review were conducted in China, and the others [ 39 , 40 , 41 ] were conducted in Iran. Although there are some observational studies suggesting the clinical benefits of acupuncture on suicidal behavior conducted in other countries [ 28 , 29 , 30 , 31 ], interventional studies targeting various ethnicities are needed to increase the possibility of a generalization. Finally, although acupuncture is considered a safe non-pharmacological treatment [ 59 ], the fact that safety data of acupuncture was reported in only three [ 35 , 36 , 37 ] of the studies included in this review is acknowledged as a methodological and ethical limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018; Lake & Turner 2017; Patel & Chatterji 2015; Vitale et al . 2021). For example, in the United States alone, the 2018 national mental health expenditures amounted to $213.3 billion, with $31 billion due to loss of work productivity (CDC 2018; Falconer et al .…”
Section: Aimmentioning
confidence: 99%
“… 1 , 2 In previous study, the authors have shown that in-person programming using intensive multimodal CIH interventions resulted in significant reduction in suicidal ideation and associated mental health risk factors, and had high Veteran engagement. 3 With the emergence of the COVID-19 pandemic, the in-person multimodal CIH intervention was pivoted to a virtual delivery of care, and in this program evaluation study the authors set out to see whether the virtual mode of delivery was similarly effective.…”
Section: Introductionmentioning
confidence: 99%